Spatial and temporal variation influences on dissolved and particulate toxic elements (As, Cd, Cr, Hg and Pb) distribution in Kuantan River, Kuantan, Pahang - Fikriah binti Faudzi (Kulliyyah of Science, International Islamic University Malaysia, 2014)
Temporal and spatial variations of selected toxic elements distributions were studied in the Kuantan River waters. Water samples from 9 sampling stations were taken from downstream of the estuary towards the upstream of Kuantan River. As, Cd, Cr, Hg and Pb were analyzed using ICP-MS after being passed through the Chelex-100 and Teflon Bomb digestion processes for dissolved and particulate fractions, respectively. Dissolved elements concentrations measured were varied from 4.650 to 39.864 µg L-1 for As, not detectable (ND) to 0.037 µg L-1 for Cd, 0.309 to 4.981 µg L-1 for Cr, ND to 0.011 µg L-1 for Hg and 2.011 to 19.983 µg L-1 for Pb, respectively. The concentration of particulate As, Cd, Cr, Hg and Pb were in the range of 0.650 to 86.087 mg L-1, ND to 14.480 mg L-1, 6.047 to 271.497 mg L-1, ND to 5.873 mg L-1 and 0.646 to 174.859 mg L-1, respectively. The distribution of the elements in dissolved and particulate fractions were found influenced by the rainy season and low-rainy season. Higher concentration of the dissolved elements were found mainly in October 2102 and particulate elements concentration mostly higher in May 2012. The toxic elements studied in Kuantan River waters were still below the Interim Marine Water Quality Standard (IMWQS) permissible limits. The order of Log Kd found in this river, Pb > As > Cr > Cd > Hg confirmed that Pb, As and Cr have the strongest affinity to become suspended particulate matter and suggested that dissolved phase was Cd and Hg as major carrier in the water columns.